From 9d25989eac2b2292550cdc6450cfe4ddb721fc8f Mon Sep 17 00:00:00 2001 From: Orestis Malaspinas <orestis.malaspinas@hesge.ch> Date: Tue, 26 Sep 2017 18:48:31 +0200 Subject: [PATCH] correction typo --- cours.tex | 2 +- 1 file changed, 1 insertion(+), 1 deletion(-) diff --git a/cours.tex b/cours.tex index 4f19b8a..6a11678 100644 --- a/cours.tex +++ b/cours.tex @@ -415,7 +415,7 @@ La somme $\sum_{i=0}^n i=n(n+1)/2$}. Et donc en prenant la limite pour $n\righta A^i=\lim\limits_{n\rightarrow\infty}\frac{n-1}{2n}=\frac{1}{2}. \end{equation} -\item $A^s(n)=\delta\sum_{i=0}^{n-1} x_i=\delta\sum_{i=0}^{n-1}\frac{i+1}{n}=\delta\sum_{i=0}^{n}\frac{i}{n}=\frac{n(n+1)}{2n^2}=\frac{n+1}{2n}$. Et donc en prenant la limite pour $n\rightarrow\infty$ il vient +\item $A^s(n)=\delta\sum_{i=0}^{n-1} x_{i+1}=\delta\sum_{i=0}^{n-1}\frac{i+1}{n}=\delta\sum_{i=0}^{n}\frac{i}{n}=\frac{n(n+1)}{2n^2}=\frac{n+1}{2n}$. Et donc en prenant la limite pour $n\rightarrow\infty$ il vient \begin{equation} A^s=\lim\limits_{n\rightarrow\infty}\frac{n+1}{2n}=\frac{1}{2}. \end{equation} -- GitLab